2021
DOI: 10.3390/agriculture11100966
|View full text |Cite
|
Sign up to set email alerts
|

Priming with Humic Acid to Reverse Ageing Damage in Soybean [Glycine max (L.) Merrill.] Seeds

Abstract: Soybean seed vigour declines with increase in storage duration, due to ageing, which can be alleviated through seed priming. The objective of this study was to investigate the effects of Humic acid (HA) priming on germination, vigour and seedling performance under laboratory and greenhouse conditions with two soil moisture level [50% and 80% field capacity (FC)]. Seeds stored for 12 months having 60% germination were primed either with 0.2 g/L HA solution or distilled water (hydro-primed) at 25 °C for 1, 3, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Seed bio-priming was conducted using the aforementioned liquid bacterial suspensions at 25 °C for 5 h, under dark conditions. After priming, seeds were rinsed thoroughly with distilled water, and dried on sterile filter paper at room temperature for 72 h [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seed bio-priming was conducted using the aforementioned liquid bacterial suspensions at 25 °C for 5 h, under dark conditions. After priming, seeds were rinsed thoroughly with distilled water, and dried on sterile filter paper at room temperature for 72 h [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ali et al (2020) reported that Humic acid exhibited most impacts on the seedling vigour index in sorghum plant. According to Weerasekara et al (2021) priming soybean seeds treated with humic acid for 3,5 and 7 hours which enhances the germination with the increase of time and increases the seedling vigour index as compared to control.…”
Section: Vigour Index-1 (Vi-1) and Vigour Index-2 (Vi-2)mentioning
confidence: 99%
“…has a special function in supplying the world's protein and calorie needs (Messina, 2022). One of the main issues with soybean seed storage is thought to be seed aging (Weerasekara et al, 2021). Membrane degradation due to lipid peroxidation is the rst event that occurs during seed aging.…”
Section: Introductionmentioning
confidence: 99%